The Strategy to Increase Farmers Income and Production of Coffee Cultivation Marketing in Buton - Wa Ode Al Zarliani; Muhamad Chairul Basrun Umanailo (AGRISAINS: Jurnal Ilmiah Magister Agribisnis, 2023)
The aim of this study is to determine the effect of land area, seeds, labor, fertilizers, pesticides and on coffee productivity. The population were all farmers who worked on coffee production, approximately around 470 people. Determination of the sample is done by simple random sampling method by taking 10% of the population, in order to obtain a total sample of 47 respondents. Furthermore, the data were tabulated and analyzed using multiple linear regression analysis techniques. The results showed that there is an effect of production factors simultaneously on productivity of coffee with an effect of 75.9% and the remaining 24.1%% is influenced by other factors. Land significance value (X1) = 0.009, seeds (X2) = 0.040, Total labor (X3) = 0.981, Fertilizer (X4) = 0.013, pesticides X5 = 0.000. From these results, labor does not have a significant effect while land area, seeds, fertilizers, and pesticides have a significant effect on coffee productivity with the Regression equation Y= 1370.989 -802.119 X1 + 11.107 X2 -101 X3 + 1.010 X4 + 519.958 X5 + e. The market of the coffee industry in Kaongkeongkea district consists of two types of trade flow, first, farmers to collectors to wholesalers then to exporters.  Second, farmers directly to wholesalers and then to exporters.